PENGARUH TATA KELOLA PERUSAHAAN DAN FAKTOR LAINNYA TERHADAP INTEGRITAS LAPORAN KEUANGAN - Haryanto, Dhisca; Mungniyati, Mungniyati (E-Jurnal Akuntansi TSM, 2023)
By the end of 2022, there are 828 companies whose shares are officially listed and can be traded on the Indonesia Stock Exchange. Investors can find out the company's financial performance by analyzing the integrity of the financial statements. The purpose of this research is to obtain empirical evidence about the effect of institutional ownership, managerial ownership, audit committee, independent commissioner, industry-specialist accounting firm, audit tenure, leverage, and company size on the integrity of financial statements. The object of this research is energy, consumer cyclicals, and consumer non-cyclicals sector companies listed on the Indonesia Stock Exchange with the period from 2020 to 2022. This research used a sample of 612 data from 204 companies. The sample selection method used is purposive sampling and used multiple regression in conducting data analysis. The results of this research indicate that institutional ownership and audit committee have a negative effect on report integrity, leverage has a positive effect on the integrity of financial statements, while managerial ownership, independent commissioners, industry-specialist accounting firm, audit tenure, and company size have no effect on the integrity of financial statements.